Research of the Adaptability and Contact Characteristic of the Mechanical Model of Overrunning Clutch based on the Hertz Theory - Shi Guanglin; Chen Zhangwei; Nie Chao; Zhu Lin (Jixie chuandong)
Taking the roller-type overrunning clutch as study object,based on the contact theory of Hertz,the contact stress between the key driving parts of the roller overrunning clutch is analyzed and studied.First,by analyzing the two common mechanical models of the overrunning clutch,the positive pressure P between the corresponding contact pair is obtained and then the Hertz stress value is calculated. Then,the application conditions of two mechanical methods are put forward through combining the contact optimization theory of Hertz. Besides,several parameters,such as contact stress,sliding distance that can reflect the contact characteristics of contact pair are obtained with the application of the finite element analysis software ANSYS,which actually verifies the adaptive conditions of two mechanical methods. The research results indicate that mechanical analysis method,which takes the coefficient of friction into consideration,is much more appropriate to the theoretical calculation,and the idealized line contact analysis model is suitable for the actual working condition,which provides a solid theoretical foundation for further understanding of the overrunning clutch operating characteristics and follow-up optimization design.